The Use of Deixis in the Traditional Pantun (Umpasa Mangampu) of Batak Toba - Achmad Yuhdi; Getsby Lewi Debora Pandiangan (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
The purpose of this study is to describe the types of deixis in the traditional pantun "Umpasa Mangampu" in the Toba Batak tribe. The method used in this research is descriptive method. The data in this study are the traditional pantun "Umpasa Mangampu" in the Toba Batak tribe, namely person deixis, time deixis, and place deixis. The data source in this research is the traditional rhyme "Umpasa Mangampu" of the Toba Batak tribe. Data collection was carried out by reading the entire Toba Batak Traditional Pantun repeatedly to identify the types contained in the pantun, noting all words related to deixis in the Toba Batak traditional pantun, marking (underlining) the part of the word or sentences in rhymes related to the types of deixis. Data analysis was carried out by identifying, classifying, analyzing/interpreting, and concluding the results of the analysis. The results of this study areThere are 4 forms of persona deixis, 2 forms of time deixis, and 1 form of place deixis.